The Anatomy of a Malpractice Lawsuit - Pradeep K Attaluri; Peter J Wirth; Steven P Moura; Ellen C Shaffrey; Venkat K Rao (Aesthetic Surgery Journal Open Forum, 2023)
Abstract Medical malpractice lawsuits can be a source of emotional, physical, and financial distress for both providers and patients. A thorough understanding of the medical malpractice process's history and current landscape will help providers navigate malpractice challenges. Given the impact and prevalence of medical malpractice, in this paper, the authors sought to dissect the intricate anatomy of a medical malpractice lawsuit. This includes a comprehensive and detailed report of tort reform, the criteria of a medical malpractice suit, and a description of the court proceedings. In addition, the authors also performed an extensive review of the medicolegal literature and have provided recommendations for healthcare providers to avoid these lawsuits in their practice. Level of Evidence: 5